FIRST FIND OF GARNET WITH ZONED BIREFRINGENCE IN MATERIAL FROM THE UDACHNAYA KIMBERLITE PIPE YAKUTIA - Barashkov Yu.P.; Matsyuk S.S.; Talnikova S.B. (My University, 1990)
We were the first to investigate the internal structure of garnet grains from a concentrate derived from the Udachnaya kimberlite pipe. In this paper we describe garnets which, in contrast to those described previously, exhibit an anomalous zoning of birefringence. The zoning in the garnets is most probably primary and associated with growth layers. The anomalous birefringence in cubic crystals results from elastic stresses, which alter the zonal and sectoral distribution of the impurities. In the zoned garnets, the microimpurities in question are potassium and carbon. The fine linear zoning of the garnets is probably a sign of growth in a free space (a silicate melt) with a minimum degree of subcooling. The lack of evidence of a complete zonal structural pattern indicates that the garnets are fragments of giant crystals (at least 4 to 5 cm across). There are likely to be alternative interpretations of the patterns.